Fungal endophytes exert positive effects on colobanthus quitensis under water stress but neutral under a projected climate change scenario in Antarctica - Hereme, Rasme (2020)
Fil: Hereme, Rasme. Universidad de Talca. Instituto de Ciencias Biológicas. Talca, Chile.